Preoperative Anxiety in Elective Oncology Surgery: A Descriptive Study - Kusuma, Putu Aldi Dana; Raya, Nyoman Agus Jagat; Nurhesti, Putu Oka Yuli; Prapti, Ni Ketut Guru (Jendela Nursing Journal (JNJ), 2025)
Background: the phenomenon of cancer not only attacks the physical, but also the psychological. One of the actions to deal with physical problems is through elective oncology surgery, which often causes anxiety for patients. This anxiety cannot be considered a small thing because it can have an impact on delaying and even canceling oncology surgery. Objective: this study aims to describe the anxiety level of preoperative patients of elective oncology surgery. Methods: this study employed a descriptive observational study with a cross-sectional approach. Respondents were selected using a purposive sampling technique with specific inclusion and exclusion criteria. Data were collected through the distribution of demographic questionnaires and the Depression Anxiety Stress Scale-21 (DASS-21) questionnaire and analyzed by descriptive statistics. Results: respondents in this study totaled 106, with 56 respondents who did not experience anxiety (52.8%), 27 respondents who experienced moderate anxiety (25.5%), 12 respondents who experienced severe anxiety (11.3%), 11 respondents who experienced mild anxiety (10.4%), and no one experienced panic attacks. Conclusion: most respondents did not experience anxiety, and almost half of the respondent’s experienced anxiety from low to severe levels. Nurses are expected to innovate in providing counseling, information, and education with digital media and technology related to reducing anxiety before oncology surgery, both in the inpatient and outpatient rooms.